Ex-ante analysis of new forage alternatives for farms with dual-purpose cattle in Peru, Costa Rica, and Nicaragua - Holmann, Federico J. (1999)
The objective was to perform an ex-ante economic evaluation of new, legume-based forage alternatives available to farmers in Latin American tropical lowlands. These alternatives included grasses of the Brachiaria genus and the legumes Stylosanthes guianensis, Cratylia argentea, and Arachis pintoi. Case studies, involving farmers participating in the CIAT-led Tropileche Consortia convened by ILRI, were conducted in the forest margins of Pucallpa (Peru) and in the hillsides of the dry tropics of Esparza (Costa Rica) and Esquipulas (Nicaragua). A linear programming farm model developed by CIAT to maximize income was used for this analysis. Animal management parameters were based on farm averages at each reference site evaluated so that they represented current management conditions. Similarly, the model incorporated the prices of inputs and products typical of each country. A constant herd size was assumed for all alternatives evaluated. Production costs per kilogram of milk were estimated as the maximum expression of competitiveness, using three cow productivity parameters: the current average production per lactation (800 kg in Peru, 1,000 kg in Nicaragua, and 1,350 kg in Costa Rica); and two postulated parameters: 1,500 kg/lactation and 2,000 kg/lactation. For all forage options, key factors analyzed were (1) milk production costs resulting from implementing each forage alternative; (2) the investment required to establish each option, assuming the same number of milking cows and herd fertility; (3) the feasibility of obtaining credit with a local bank to invest in a forage alternative; and (4) the percentage of pasture area on the farm freed for other uses as a result of establishing one of the forage alternatives. Results indicated that the forage alternatives evaluated significantly improved the competitiveness of dual purpose farms in the hillsides of Nicaragua and Costa Rica, reducing the cost of producing milk between 13% and 37% with increased stocking rates, releasing up to 36% of area allocated to pastures. However, under current commercial banking conditions (real interest rates of 13% in Costa Rica and 18% in Nicaragua with payback periods of 5 years), the implementation of the options evaluated were not financially viable except for the establishment of Cratyla with sugarcane for dry-season feeding and Stylosanthes for pre-weaned calves. For all options to be implemented with commercial credit, a longer payback period was needed (8-10 years) and lower real interest rates (5-10%). The case of the forest margins of Pucallpa, was different, as none of the forage options evaluated, except Stylosanthes for pre-weaned calves, improved the competitiveness of farms under current management and production conditions due to low milk yields per cow and low proportion of herd in milk, which increased depreciation cost/cow to levels which were not viable. In addition, Pucallpa has an excess supply of forage biomass from a reduced herd inventory during the 80s and a limited fresh milk market which makes adoption of improved forages low attractive by farmers.